Implementasi Manajemen Resiko dalam upaya mewujudkan prinsip-prinsip good governance - Fanny Oktapiani; Mia Rosmiati; Lili Indrawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Organizations are faced with increasingly complex job risks, so it is necessary to apply risk management that can help organizations to reduce risks as small as possible and eliminate uncertainty in the business environment. This study aims to determine how the implementation of risk management in an effort to realize the principles of good governance in the West Bandung Regency Government, namely upholding the rule of law, transparency, caring for stakeholders, effectiveness and efficiency, accountability, and strategic vision. The research method used is descriptive qualitative with interviews and documentation as data collection instruments. The results of this study indicate that the implementation of risk management in the West Bandung Regency Government is not in accordance with existing guidelines. This is due to ineffective socialization of risk management implementation. So that SKPD does not yet understand the implementation of risk management within the West Bandung Regency Government.